2018
DOI: 10.1155/2018/7361684
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Sequencing Analysis of Islet Stellate Cell and Pancreatic Stellate Cell

Abstract: Background Our previous studies have shown that islet stellate cell (ISC), similar to pancreatic stellate cell (PSC) in phenotype and biological characters, may be responsible for the islet fibrosis in type 2 diabetes. To further identify the differences between PSC and ISC and for better understanding of the physiological function of ISC, we employed genome-wide transcriptional analysis on the PSCs and ISCs of Wistar rats. Method PSCs and ISCs from each rat were primarily cultured at the same condition. Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…We previously found that ISCs are responsible for islet fibrosis ( 14 ). However, we also demonstrated that ISCs and PSCs are similar but not identical via transcriptome sequencing ( 17 ). Compared with PSCs, ISCs exhibit lower proliferation and migration rates, are more easily to be activated by stimulators, and have fewer lipid droplets.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We previously found that ISCs are responsible for islet fibrosis ( 14 ). However, we also demonstrated that ISCs and PSCs are similar but not identical via transcriptome sequencing ( 17 ). Compared with PSCs, ISCs exhibit lower proliferation and migration rates, are more easily to be activated by stimulators, and have fewer lipid droplets.…”
Section: Discussionmentioning
confidence: 81%
“…However, they exhibit differences in cell activation, proliferation, migration, and collagen synthesis. Through transcriptome sequencing, we also found that ISCs and PSCs have similar characteristics ( 17 ). Stellate cells stay quiescent in general.…”
Section: Introductionmentioning
confidence: 85%
“…We found that insulin secretion from islets cocultured in vitro with db/m mouse ISCs was significantly increased compared to that from islets cocultured with ISCs from db/db mice. Subsequent iTRAQ protein screening of the ISCs showed that both ISCs cultured under static conditions and their supernatants showed high Wnt5a protein expression compared with diabetic ISCs [24][25][26][27][28][29][30]. e mechanisms leading to ISCs quiescence play an important role in regulating islet function via the Wnt5a-Fzd5 system and can help us understand the crosstalk between cells inside the islets of Langerhans and serve as a target for the prevention of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In pervious study, our group has compared the biological characteristics of ISCs with typical PSCs, and found that there are 32 significant differentially expressed genes between activated PSCs and activated ISCs. Due to fewer lipid droplets, ISCs appeared to be more easily activated by stimulators, and demonstrated reduced proliferation and migration abilities [34]. Therefore, the biological phenotypes of ISCs and PSCs are similar, but not completely identical.…”
Section: Discussionmentioning
confidence: 99%